Advertisements
Advertisements
Question
According to the Principle of duality, the Boolean equation
(A+ B') • (A+ 1) =A+ B' will be equivalent to ______.
Options
(A' + B) • (A'+ 1) = A' + B
(A • B') +(A • 0) = A • B'
(A' • B) +(A' • 1) =A' • B
(A' • B) +(A' • 0) =A' • B
Solution
According to the Principle of duality, the Boolean equation
A+ B') • (A+ 1) =A+ B' will be equivalent to (A • B') +(A • 0) =A • B'.
Explanation:
The principle of duality asserts that AND becomes OR and vice versa, 0 becomes and vice versa, but complement remains constant.
APPEARS IN
RELATED QUESTIONS
The dual of (X' + 1) · (Y' + 0) = Y' is ______.
The reduced expression of the Boolean function F(P, Q) = P' · + P · Q is ______.
With reference to the code given below, answer the questions that follow along with dry run/working.boolean num(int x)
{ int a=1}
for (int c=x; c>0; c/<10}
a*=10;
return (x*x%a)=x;
}
- What will the function num() return when the value of x = 25?
- What is the method num() performing?
Verify if the following proposition is a Tautology, Contradiction or Contingency using a truth table.
((A=>B)∧(B=>C))=>(A=>C)
Find the complement of the following expression and reduce it by using Boolean laws.
P•( 13 ± Q)•Q•(Q+R')
How is a decoder different from a multiplexer?
According to the Principle of duality, the Boolean equation (Aꞌ + B) • (1 + B) = Aꞌ + B will be equivalent to ______.
Distributive law states that ______.